Efektivitas Media Permainan Engklek Riang Gotong Royong (Eyang Eyong) terhadap Hasil Belajar Pendidikan Pancasila Siswa Kelas V SD 3 Menawan - Ni’mah, Aulia Ulfatun; Rondli, Wawan Shokib; Kironoratri, Lintang (Universitas Nusantara PGRI Kediri, 2025)
This study aims to evaluate the validity and effectiveness of the Eyang Eyong learning tool, which is a cheerful hopscotch game of mutual cooperation, in improving the cognitive achievement of Pancasila Education in grade V students at SD 3 Menawan. Using a quantitative approach and One Group Pretest-Posttest design, involving 23 students as participants. Data were obtained from interviews, tests, and observations. The results of the study showed that the Eyang Eyong instructional tool was proven to be feasible to use and effective in improving students' cognitive achievement. The normality test indicated that the data was normally distributed, while the Paired Sample T-Test showed an increase in value (p = 0.001). The average N-Gain value obtained was 0.5308 indicating that the progress of cognitive achievement was included in the moderate category. Based on these findings, it is recommended that innovative learning media such as Eyang Eyong be a tool to help students understand the material and improve their cognitive achievement.